Arthritis in Leprosy: A Case Report - Tumewu, Aaron; Awalia, Awalia (Gaceta Médica de Caracas, 2023)
Introduction: Despite the third most common manifestations of leprosy, musculoskeletal manifestations are still underdiagnosed in leprosy patients, causing progressing and disfiguring disabilities. Case Presentation: A 25-year-old woman presented with constant pain in both hands that had been worsening over the past month. She also reported progressive nodules over the face. Radiology revealed deformity of the second digit of her left hand and punch biopsy revealed a type II reaction of lepromatous leprosy. She later started treatment with oral steroids and a multibacillary leprosy regimen.